Theoretical and practical knowledge curriculum for European Breast Surgeons. Issue 4 (April 2020) - ,; Benn, Karen; Cardoso, Maria Joao; Catanuto, Giuseppe; Costa, Alberto; Curigliano, Giuseppe; Cserni, Gabor; Downey, Sarah; Farhadi, Jian; Gentilini, Oreste; Gulluoglu, Bahadir; Herrero, Julia Camps; et al.
Executive summary: The Breast Surgery theoretical and practical knowledge curriculum comprehensively describes the knowledge and skills expected of a fully trained breast surgeon practicing in the European Union and European Economic Area (EEA). It forms part of a range of factors that contribute to the delivery of high quality cancer care. It has been developed by a panel of experts from across Europe and has been validated by professional breast surgery societies in Europe. The curriculum maps closely to the syllabus of the Union of European Medical Specialists (UEMS) Breast Surgery Exam, the UK FRCS (breast specialist interest) curriculum and other professional standards across Europe and globally (USA Society of Surgical Oncology, SSO). It is envisioned that this will serve as the basis for breast surgery training, examination and accreditation across Europe to harmonise and raise standards as breast surgery develops as a separate discipline from its parent specialties (general surgery, gynaecology, surgical oncology and plastic surgery). The curriculum is not static but will be revised and updated by the curriculum development group of the European Breast Surgical Oncology Certification group (BRESO) every 2 years.